Performance of building integrated photovoltaic facades: Impact of exterior convective heat transfer. (1st April 2021) - Gonçalves, Juliana E.; Montazeri, Hamid; van Hooff, Twan; Saelens, Dirk
Abstract: Building integrated photovoltaic (BIPV) applications are key to increase the share of renewable energy in the built environment. A large potential for BIPV deployment is related to building facades. The assessment of BIPV facades depends on the accurate modelling of exterior convective heat transfer coefficients (eCHTC). However, eCHTC models commonly used in BIPV modelling tend to be simplified. This paper proposes a simulation framework that combines detailed computational fluid dynamics with a multi-physics BIPV model to investigate the influence of eCHTC on the performance of BIPV facades (cell temperature and power). The evaluation is performed for different building geometries, wind speeds, wind directions, solar irradiations, and ambient temperatures. The results show that local variations in eCHTC can cause variations in cell temperature up to 42 ° C between the BIPV modules across the facade. These temperature differences are associated with differences in power up to 17% across the BIPV facade. In general, lower temperatures (and higher power output) occur near the edges of the facade while higher temperatures (and lower power output) occur at the middle and at the bottom of the facade. Therefore, a detailed assessment of wind effects is recommended in order to verify the local operating conditions of the BIPV modules. The framework and findings presented in this work are relevant for applications in which the knowledge of the local behaviour is important, such as degradation studies. Highlights: Impact of convective heat transfer on building-integrated photovoltaic facades. A detailed analysis of the impact of building geometry, wind speed and direction. Numerical analyses using a multi-physics model & computational fluid dynamics. The local convective heat transfer significantly affects cell temperature and power. Variations in cell temperature and power can go up to 42 °C and 17%, respectively.